2022
DOI: 10.1557/s43578-022-00798-6
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and stainability of new-generation denture base materials after brushing and coffee thermocycling

Abstract: Disk-shaped specimens were prepared from additively (NX and DT), subtractively (MZ), and conventionally manufactured denture base resins (CV). Surface roughness and color coordinates were measured after polishing, simulated brushing, and coffee thermocycling, while surface roughness was also measured before polishing. Polishing reduced the surface roughness of all materials. Brushing and coffee thermocycling increased the surface roughness of only DT. CV had the highest susceptibility to consecutive brushing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Given that the present study was the first on the R a and stainability of pink GSM, a priori power analysis based on the results of previous studies could not be performed, which could be considered as a limitation. Nevertheless, significant differences were observed among tested materials and the number of specimens in each group was based on previous studies on the R a and discoloration of additively and subtractively manufactured PMMAs 5,6,9,20 ; one of those studies reported the results of a priori power analysis based on a pilot study. 20 In addition, post hoc power analyses were performed for each parameter investigated and the sample size was deemed adequate for a minimum of 83% power with a minimum effect size of 0.62 and α = 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that the present study was the first on the R a and stainability of pink GSM, a priori power analysis based on the results of previous studies could not be performed, which could be considered as a limitation. Nevertheless, significant differences were observed among tested materials and the number of specimens in each group was based on previous studies on the R a and discoloration of additively and subtractively manufactured PMMAs 5,6,9,20 ; one of those studies reported the results of a priori power analysis based on a pilot study. 20 In addition, post hoc power analyses were performed for each parameter investigated and the sample size was deemed adequate for a minimum of 83% power with a minimum effect size of 0.62 and α = 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…A digital spectrophotometer (CM-26d; Konica Minolta), which has a Commission International de I'Eclairage (CIE) D65 illuminant and uses CIE Standard (2-degree) human observer characteristics, was used to measure the color coordinates of each specimen on a gray background. 5,9,20 All measurements were performed in the same temperature-and humidity-controlled room with daylight by a single operator and the spectrophotometer was calibrated before each scan.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations